Predicting the Case of COVID-19 in Indonesia using Neural Prophet Model - Efraim Yahya Wijaya; Alethea Suryadibrata (IJNMT (International Journal of New Media Technology), 2022)
Since the initial entry of the COVID-19 virus in Indonesia, the spread of cases increased significantly. This has a huge impact on hospitals that serve chronic COVID-19 patient. There are several ways that the government used to suppresses the spread of COVID-19 case in Indonesia, such as making PPKM policies and providing vaccinations. Through this research, the prediction method is used to find increasing and decreasing of COVID-19 cases using the Neural Prophet model. Then the model will be compared with the Facebook Prophet as comparison model. In this study dataset is used from (covid19.go.id) which was taken on 23 June 2022 with scraping technique. The results of this study indicate that the Neural Prophet model has better value in RMSE, and MAE compared to the Facebook Prophet.